Effect of spatial confinement on luminescence of Y3Al5O12 nano-particles doped with chromium ions - ERDEM, MURAT (ELSEVIER, 2013)
We have studied the spectroscopic properties of four nano-powder samples of Y3Al5O12: Cr particles with diameters ranging from 28 nm to 250 nm. For each sample we have measured accurately the emission spectrum in a wide range of temperatures ranging from 30 to more than 600 K. The spectra generally consisted of the R-lines narrow spectral emission and of the accompanying vibronic side-bands. We noted the increase of the vibronic emission intensity with respect to the R-line intensity going from the larger to the shorter diameter powders. For each sample we have also measured the decay patterns of the excited Cr ions following a pulsed excitation. These measurements were conducted in the same temperature range (30-600 K) in order to fully characterize the samples examined. We have confirmed the fact that such patterns vary considerably with the size of the nano-particle, so that they may be considered signatures of these sizes. In the discussion of the experimental results we present some thoughts on the information provided by the data and in the conclusions we elaborate these thoughts and provide a coherent picture of the processes at work. (C) 2013 Elsevier B.V. All rights reserved.
Keywords: Spatial confinement; Cr-doped YAG; Low frequency phonons; Vibronic side-bands; GARNET; CERAMICS